THE EFFECT OF GIVING BLOCK GAMAL LEAF ON BLOOD GLUCOSE LEVELS OF BALI CATTLE ANESTRUS - Mary Renata Devi Natalivia; Samsuri; I Made Merdana; Luh Made Sudimartini; I Nyoman Sulabda; Anak Agung Sagung Kendran (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Anestrus is a condition in female animals that do not show symptoms of estrus for a long period of time. Anestrus is a frequent cause of infertility in cows. Gamal leaves in the cow's rumen are expected to optimize the fermentation process so that they can increase volatile fatty acids (VFA). The expected total VFA product increases the propionate ratio. Increasing the propionate ratio has an effect on increasing gluconegenesis in the liver, resulting in an increase in blood glucose. This study aims to determine the impact of administering gamal leaf blocks on blood glucose levels of Bali cattle experiencing anestrus. This research used 6 anestrus Bali cattle as objects selected using purposive sampling. The six cows were given block treatment for 2 weeks. After sampling was carried out on the 10th day after treatment and the 20th day after treatment, the results showed that administering a gliricidia leaf block for 14 days had no significant effect on increasing blood glucose levels in anestrus Bali cattle.